A Longitudinal Examination of Alcohol Problems and Cyber, Psychological, and Physical Dating Abuse: The Moderating Role of Emotion Dysregulation - Brem, Meagan J. (Journal of interpersonal violence, 2021)
Given the prevalence of technology, cyber dating abuse (DA) emerged as an important area of empirical inquiry. Cross-sectional data linked cyber DA perpetration to alcohol problems and psychological and physical DA perpetration. However, the longitudinal relations among these constructs are unknown. DA theory and research suggested that higher levels of aggressogenic traits (e.g., emotion dysregulation) increased the likelihood that alcohol problems and DA co-occur; this conceptual model may extend to cyber DA. We collected self-report data from 578 college students at baseline (T1) and 3 months later (T2) to test the hypothesis that T1 alcohol problems would predict T2 psychological, physical, and cyber DA for students with high, but not low, emotion dysregulation. We also hypothesized that T1 cyber DA would predict T2 psychological and physical DA. We conducted path analyses in Mplus and used the Johnson-Neyman technique to probe significant interactions. Results indicated that alcohol problems predicted psychological and physical DA for college students with high and average emotion dysregulation only. Alcohol problems did not predict cyber DA independently or in conjunction with emotion dysregulation. Cyber DA predicted psychological and physical DA. Results extend DA conceptualizations and highlight the importance of targeting emotion dysregulation in college DA intervention programs.